CPS MODEL ON CREATIVE THINKING SKILLS IN MATHEMATICS PROBLEM SOLVING IN TERMS OF SELF-REGULATED LEARNING - Ellya Masturina Hamid; Isnarto Isnarto; Iqbal Kharisudin (JME (Journal of Mathematics Education), 2024)
Creative thinking and problem solving skills are essential in facing the challenges of the 21st century. This study aims to (1) test the effectiveness of the contextual approach CPS model in improving creative thinking skills in mathematics problem solving and (2) describe creative thinking skills in mathematics problem solving in terms of Self Regulated Learning (SRL). This type of research is a mixed method research that combines quantitative and qualitative research methods sequentially. In this study, 6 research subjects were taken based on the level of SRL in class XI students of SMA N 5 Semarang. The results showed that (1) contextual approach CPS learning is effective in improving creative thinking ability in mathematics problem solving, and (2) research subjects with high SRL category were able to fulfill all indicators of creative thinking ability in mathematics problem solving, namely fluency, flexibility and novelty; research subjects with moderate SRL category only fulfilled two indicators of creative thinking ability in mathematics problem solving, namely fluency, and flexibility; research subjects with low SRL category were only able to fulfill the indicator of creative thinking ability in mathematics problem solving, namely fluency.